Helminths of small rodents (Heteromyidae and Cricetidae) in the Yucatan Peninsula, Mexico: an integrative taxonomic approach to their inventory - Panti-May, Jesús Alonso; Moguel-Chin, Wilson Isaias; Hernández-Mena, David Iván; Cárdenas-Vargas, Miguel Humberto; Torres-Castro, Marco; García-Prieto, Luis; Digiani, Maria Celina; Hernández-Betancourt, Silvia F.; Vidal-Martínez, Víctor Manuel (Zootaxa, 2023)
In this survey, we inventoried the helminths of heteromyid and cricetid rodents captured in the Yucatan Peninsula from 2017 to 2019. Helminths were identified using morphological techniques (clearing, staining, and scanning electron microscopy). Also, the 28S rRNA gene of individuals from several helminth taxa was successfully amplified and sequenced. To confirm the identification at the generic level, and in some cases at the specific level, and the genealogical relationships of the parasites, phylogenetic analyses were performed with the new 28S sequences. We identified 22 species of helminths including three trematodes (Brachylaimidae, Dicrocoeliidae, and Microphallidae), five cestodes (Davaineidae, Hymenolepididae, and Taeniidae), and 14 nematodes (Trichuridae, Ancylostomatidae, Ornithostrongylidae, Heligmonellidae, and Oxyuridae) from Heteromys gaumeri (Heteromyidae), Ototylomys phyllotis, Oligoryzomys fulvescens, Peromyscus yucatanicus, Sigmodon toltecus, and Reithrodontomys gracilis (Cricetidae). The overall frequency of infection in small rodents was 84.1% (143/170); all specimens of H. gaumeri, S. toltecus and Ol. fulvescens were infected with helminths. In total, we provided 46 new sequences of the 28S gene from 17 species of helminths. Seven species are likely undescribed species, six are reported for the first time in rodents from Mexico, and 12 are new host records in the Americas. Before this study, 87 taxa of helminths had been reported from 35 cricetid and 12 heteromyid species in 21 Mexican states. Our findings increase to 93 the helminth taxa in these rodents, and to 36 the cricetid species parasitized by helminths. This large scale-survey is the first to use an integrative approach to inventory the helminths of wild small rodents in Mexico.